2011
DOI: 10.4051/ibc.2011.3.3.0010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Hash Function Using DNA-Based XOR Logic Reveals Unexpected Behavior of the LuxR Promoter

Abstract: SYNOPSIS Introduction:Hash functions are computer algorithms that protect information and secure transactions. In response to the NIST"s "International Call for Hash Function", we developed a biological hash function using the computing capabilities of bacteria. We designed a DNA-based XOR logic gate that allows bacterial colonies arranged in a series on an agar plate to perform hash function calculations. Results and Discussion: In order to provide each colony with adequate time to process inputs and perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In Synechocystis , an 8-fold increase in fluorescence was observed in presence of LuxR compared to constitutive levels ( Supplementary Figure S2 ), and the induction was shown to be independent of AHLs. Similarly, in E. coli , it was shown that backwards transcription from the P luxR can occur by binding of the LuxR to the promoter in the absence of AHLs ( 49 ). The regulated expression of the heterologous P λcI promoter was also tested in Synechocystis.…”
Section: Resultsmentioning
confidence: 99%
“…In Synechocystis , an 8-fold increase in fluorescence was observed in presence of LuxR compared to constitutive levels ( Supplementary Figure S2 ), and the induction was shown to be independent of AHLs. Similarly, in E. coli , it was shown that backwards transcription from the P luxR can occur by binding of the LuxR to the promoter in the absence of AHLs ( 49 ). The regulated expression of the heterologous P λcI promoter was also tested in Synechocystis.…”
Section: Resultsmentioning
confidence: 99%